2021
DOI: 10.1080/10942912.2021.1873364
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Fast Foods Consumption: a Review

Abstract: While all groups are affected by the COVID-19 pandemic, the aged people as well as those with underlying chronic medical conditions are at the greatest risk. The higher adherence to refined carbohydrate diets, sweats, and saturated fats contributes to the prevalence of obesity and type 2 diabetes; these disorders increase the risk for severe COVID-19 morbidity and mortality. Fast food consumption activates the intrinsic immune system and impairs adaptive immunity, leading to chronic inflammation and impaired h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
0
19
0
1
Order By: Relevance
“…The percentage of individuals with the appropriate consumption of whole grains did not exceed 40% in G1 and G2, while in G3 it was significantly higher (47.5%), but still insufficient. The positive influence of whole grains on improving immune function is observed [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of individuals with the appropriate consumption of whole grains did not exceed 40% in G1 and G2, while in G3 it was significantly higher (47.5%), but still insufficient. The positive influence of whole grains on improving immune function is observed [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, poor eating habits were noticed such as changes in meal frequency and increased snacking with comfort foods (food bringing emotional comfort). It shows that alteration in dietary habits during the pandemic are at higher risk of further complications ( Bohlouli et al, 2021 ).…”
Section: Influence Of Junk Food During Covid-19 Pandemicmentioning
confidence: 99%
“…Hishiki et al [63] indicated that a probiotic strain of LAB, Pediococcus acidilactici K15, has a beneficial effect on the prevention of respiratory tract infections just for children who eat less than two fermented food or yogurt items per week. According to findings, probiotic-based and fermented foods are beneficial for the prevention and treatment of viral diseases, however, these effects should be investigated in SARS-CoV2 infection [64].…”
Section: Major Effects Of Probiotic-containing and Fermented Foods On Viral Infectionsmentioning
confidence: 99%